2019
DOI: 10.1007/978-3-030-21462-3_13
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Input Data Formalisation in Relational Concept Analysis for a Data Model with a Ternary Relation

Abstract: 0000−0001−6542−3360] , Alain Gutierrez, Marianne Huchard 2[0000−0002−6309−7503] , Florence Le Ber 3[0000−0002−2415−7606] , Samira Sarter 5[0000−0001−5115−0824] , Pierre Silvie 1,4[0000−0002−3406−6230] , and Pierre Martin 1[0000−0002−4874−5795]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Although developed for KB, they are general and apply to similar datasets and research questions. Solutions for applying FCA/RCA in data models including ternary relationships have been proposed [ 142 ]. They consider several encodings of ternary relationships, including solutions using binary relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although developed for KB, they are general and apply to similar datasets and research questions. Solutions for applying FCA/RCA in data models including ternary relationships have been proposed [ 142 ]. They consider several encodings of ternary relationships, including solutions using binary relationships.…”
Section: Discussionmentioning
confidence: 99%
“…FCA and RCA have been applied to KB excerpts at different stages in its building process. In [ 142 ], the uses of six plants selected by experts for their recognized qualities against Aspergillus were analyzed to answer the question: ‘Knowing the recognized benefits of Hyptis suaveolens in the protection of Arachis hypogaea against Aspergillus parasiticus , which other plants could alternatively be used?’. The RCA-based classification and plant grouping readily revealed that Ocimum gratissimum could replace Hyptis suaveolens to protect Arachis hypogaea against Aspergillus ochraceus and Aspergillus flavus .…”
Section: Discussionmentioning
confidence: 99%
“…This requires deciding how data are separated in formal and relational contexts, and how to represent n-ary relations, e.g. ternary relations, a topic we studied in [10]. Life sciences data raise other issues, such as indeterminate species [9].…”
Section: Related Workmentioning
confidence: 99%
“…As said before, these two datasets have already been studied [15,29,38]. In this paper, we propose a synthesis of observations made during these earlier studies, with enhanced datasets, taking into account more information or applied to the whole initial data rather than to an excerpt.…”
Section: Introductionmentioning
confidence: 99%
“…for the fuzzy semantic annotation of web resources [13], or for the analysis and reengineering of software models [14] and semantic wikis [47]. In previous works, we have applied RCA for exploring hydroecological [15,38] and agricultural data [29], the two domains considered in the following.…”
Section: Introductionmentioning
confidence: 99%